METHODOLOGICAL POSSIBILITIES OF TURNING ENGLISH INTO PRIMARY CLASSES ON THE BASIS OF DIDACTIC MEANS - Yuldasheva Zumradxon Turgunpolatovna (Journals Park Publishing, 2024)
This article will consider the methodological possibilities of teaching English to primary classes with the integration of didactic tools. The article examines the practical applications of visual weapons, educational games, interactive software, and multimedia resources, relying on theoretical foundations such as constructivism, socio-cultural theories, and communicative language teaching. In addition, it considers pedagogical considerations of moral, cultural and contextual importance in the selection and use of didactic tools.
Keywords: foreign language, education, elementary learning processes, didactic views, English.